Passive phosphorus capture in biofiltration context: nitrate impact on the performance. Issue 28 (18th December 2020) - Hamidou, Soureyatou; Dubé, Rino; Lessard, Paul; Buelna, Gerardo; Dorea, Caetano C.; LeBihan, Yann
ABSTRACT: Research on the development of a passive phosphorus entrapment process characterized by biofilters with active wood-based media impregnated with iron hydroxide has been conducted. Phosphorus removal was done by sorption which includes adsorption, exchange of ions and precipitation. Experiments were performed in order to investigate the effect of nitrate, generally present at the end of secondary treatment, on the phosphorus removal performance. Columns tests were performed with anaerobic activated wood-based media and immersion over a period of 150 days. Columns were fed for 32 days with a synthetic solution of 5 mg P L −1 . Different concentrations of nitrate (5, 10 and 25 mg N-NO3 L −1 ) were then applied on three columns (C2, C3 and C4 ), column C1 serving as a control. Results showed total phosphorus (TP) removal efficiencies of 96.9%, 81.7%, 70.6% and 75.7%, respectively, for C1, C2, C3 and C4 . Addition of nitrate increases the oxidoreduction potential (ORP). This results in an inhibition of the reductive dissolution, characterized by a decrease in the release of ferrous ions. Simultaneous denitrification occurs within the columns. It is both biological and chemical through the oxidation of ferrous ions by NO2, produced during biological denitrification. Furthermore, bacterial identification tests have highlighted the presence of iron-related bacteria ( Pseudomonas, Thiobacillus, Enteric bacteria, e.g. E. coli ), slym forming bacteria, sulphate reducing bacteria and denitrifying microorganisms such as Pseudomonas and E. bacteria in biofilters. GRAPHICAL ABSTRACT: UF0001